INVESTIGATION OF THE SUBJECT-SPATIAL ENVIRONMENT OF THE SCHOOL BY THE METHOD OF SEMANTIC DIFFERENTIAL - I. A. Vinogradova; E. V. Ivanova; O. V. Nesterova (Russian State Vocational Pedagogical University, 2018)
Introduction. Physical and psychological parameters of the school space have a significant impact on the motivation of a learning process and its results. Specificity of the school environment, its atmosphere and surroundings determine the meaning and nature of learning, a vector and activity of development and self-development of participants in the educational process, and determine their actions in it. This circumstance makes it necessary to develop reliable diagnostic tools that enable to study the environment of educational organizations, its impact on quality of activity and successful communications of school students and teachers.The aims of this article are the following: to reveal the possibilities of the comprehensive diagnostics of the school environment and its different spatial zones; to identify and compare the perception of school space by different participants of educational relations.Methodology and research methods. The main method of the research is Ch. Osgood's Semantic Differential (SD) modified in the context of the features of the general stages of education. Data processing was carried out using the mid-group analysis, cross-group relations, and cluster and regression analysis using the method of step selection. Student's t-test, Cronbach's Alpha and Pearson's Correlation were applied to test reliability and validity of the method of semantic differential and the received results.Results and scientific novelty. The level of suitability of a classical measurement technique by Ch. Osgood for the task solution is found out. Dichotomic pairs of characteristics of the subject-spatial environment of the school are singled out; the authors' version of semantic differential is designed having applied those pairs. The hierarchical organization of the parameters of the subject-spatial environment of the school is proved; the level of comfort acts as the parameter integrating all its characteristics, which, however, is unequally regarded by students and teachers (total number of respondents sample was N = 661). Significant differences in the estimates of the subject-spatial environment in the groups of students and teachers (from p < 0.05 to p < 0.000) are established and described. Regression formulas for each group of participants of educational process are proposed; which can be followed to estimate optimum values of comfortable learning and professional-pedagogical activity as well as to adjust subject space of a certain school.Practical significance. The developed and approved diagnostic tool makes it possible to attract external and internal experts; to obtain the quantitative data that expand the field of application of mathematical statistics; and also can become a basis of the organization of longitudinal and comparative studies of the subject space of school. Regular monitoring can be considered as a predictor of psychological well-being conditions of an educational institution since the timely and exact estimates provide adoption of operational and effective measures for improvement of the environment of the educational organization in order to strengthen the efficiency of its performance and get better results of educational activity.